Video reflexive ethnography as an intervention to improve oral anti-cancer agent patient education: A pilot study - Milisa Manojlovich; Amna Rizvi-Toner; Ryan DasGupta; Karen Farris; Chris Friese; Diana Kostoff; Emily Mackler; Vanessa Millisor; Marita G. Titler (Elsevier, 2023)
Objective: Oral anticancer agents (OAAs) are associated with side effects that interfere with medication adherence, despite patient education regarding side effect management. Video reflexive ethnography (VRE) captures care processes on video that allow participants to learn from videos. The purpose of this pilot study was to assess the usefulness and impact of VRE on improving OAA education. Methods: This qualitative study was conducted in a pharmacist-managed OAA clinic: two pharmacists and four patients participated. We filmed each pharmacist providing education to two patients. We conducted patient interviews and one reflexivity session with both pharmacists to learn participants' perspectives. We used thematic content analysis to analyze data. Results: Two themes emerged: what patients liked/helped, and things that were unclear. Patients liked instructions on temperature taking, directions to safely handle and store OAAs. Unclear areas included knowing the timing of the worst side effects.During the reflexivity session, pharmacists found patients' comments useful to improve their practice. Conclusion: VRE was acceptable to pharmacists and patients. Pharmacists recognized VRE as a helpful technique to improve patient education on OAAs. Innovation: The use of video enables participants to scrutinize and reshape their practices, making VRE a powerful innovation and adjunct to quality improvement initiatives.